Strand 2: Act On Line Project: Networked Learning practice on Internet/WWW - Garcia, Marilene Santana Santos; Maia, Carmem (Proceedings of the International Conference on Networked Learning, 1998)
Act On-line Project has been designed to supply emerging requests for continued professional and cultural background. It offers assistance (pedagogical and technological) for constructing short length courses for Internet/WWW environment aiming at reaching the internal public, composed of Universidade Anhembi Morumbi students and teachers, and the outside public as well. For the internal public, an Internet environment has been structured in order that students can benefit from independent study combination, both in classroom and on Internet possibilities. Through Act On-line Project, Universidade Anhembi Morumbi is investing in methodological research to create distance learning environments on the Web, emphasizing the exploitation of interactive communication and information tools to support on line courses and on line consultation for its students.